Sutan Sjahrir's Footprint in Egypt, Middle East: A History That Is Almost Forgotten - Herdi Sahrasad; TI Aisyah; Dedy Tabrani; Mohamad Asrori Mulky (Budapest International Research and Critics University, 2020)
This article argues that the Indonesian people will never forget the services and roles of Egypt, the country that first recognized Indonesian independence. History recorded that the first recognition of the sovereignty of Indonesia is not done by Western countries, especially the United States who often claim him as a promoter of freedom and human rights (human rights). Indonesia's struggle for independence is supported firstly and heroically by the Muslim countries in the Arab, not others because of the spiritual-emotional relationships and civil Islam in all of the countries and nations. At that time, Arab world have felt, how strong ukhuwah Islamiyyah (Islamic solidarity and linkage) between the Indonesian people and with Arab nations who are struggling for their independence.